Developing Instruments to Measure Long Passing and Shooting Skills of the Football School Students of Medan City - Nusri, Ardi; Setijono, Hari; Rahayu, Tandiyo; Soegiyanto, Soegiyanto (Universitas Negeri Semarang, 2018)
The preliminary study gives the result that the Football School (SSB) trainers in Medan City do not yet have adequate long passing and shooting skill measuring instruments. They rely on observation only in assessing their students’ achievement. Assessment that is based on observation has many weaknesses, one of which is the high element of subjectivity. This study aims to produce instruments to measure the studentss long passing and shooting skills. This is a research and development study. The authors used experimental methods in this study through the following steps, (a) draft development, (b) validation, (c) small group tryouts, and (d) extended group trials. The small group tryouts were conducted three times and the extended group trial was administered once. In the extended group trial the authors involved 150 male students of 8 SSB. Based on factorial analysis (validity test) and test and retest (reliability test), the result is that the long passing and shooting instruments are valid (P <000) and reliable (R> 0.6). Thus, this measuring instrument is very good for measuring long passing and shooting skills of the SSB students.